The influence of plastic extrusion blow molding parameters on waste reduction - Kamaruddin, S. (Asian Research Publishing Network, 2016)
Growing demands of plastics deriving environmental and social concern on the plastics contained in municipal waste. Comprehending to this fact, this study emphasizes on minimization of plastic wastes during extrusion blow molding process by controlling the processing parameters including parison thickness, chiller temperature, melting temperature and extruder speed. L8 Taguchi orthogonal array (OA), signal to noise (S/N) ratio and analysis of variance (ANOVA) were conducted to investigate the influence of numerous blow moulding processing parameters on the plastic wastes. Â©2006-2016 Asian Research Publishing Network (ARPN).